Gender and Employment in the COVID-19 Recession : Evidence on 'She-cessions' - Bluedorn, John (IMF Working Papers; Working Paper ;, 2021)
Early evidence on the pandemic's effects pointed to women's employment falling disproportionately, leading observers to call a 'she-cession.' This paper documents the extent and persistence of this phenomenon in a quarterly sample of 38 advanced and emerging market economies. We show that there is a large degree of heterogeneity across countries, with over half to two-thirds exhibiting larger declines in women's than men's employment rates. These gender differences in COVID-19's effects are typically short-lived, lasting only a quarter or two on average. We also show that she-cessions are strongly related to COVID-19's impacts on gender shares in employment within sectors.